Immunomodulatory asthma therapy in the equine animal model: A dose‐response study and evaluation of a long‐term effect. Issue 3 (29th May 2019) - Klier, John; Bartl, Carolin; Geuder, Sabine; Geh, Katharina J.; Reese, Sven; Goehring, Lutz S.; Winter, Gerhard; Gehlen, Heidrun
Abstract: Introduction: Equine asthma represents a naturally occurring animal model for human allergic neutrophilic asthma. Inhalative nanoparticle‐bound cytosine‐phosphate‐guanosine (CpG‐GNP) immunotherapy, independent of specific allergens, has already shown promising clinical and immunological results in previous studies and offers the possibility to treat the underlying cause of the disease. This study analyses the relationship between dose and response, and evaluates a possible long‐term effect. Methods: In the prospective, randomised, double‐blind clinical field study, 29 horses suffering from equine asthma received 10 inhalation treatments with either 187.5 µg CpG‐GNP (CpG single dose [CpGsd]; n = 11), 375 µg CpG‐GNP double dose (CpG double dose [CpGdd]; n = 9) (q48h for 20 days) or 1600 µg beclomethasone (n = 9) (q24h for 10 days). Each horse was examined three times: before the treatment (I), immediately after the 10 inhalations (II), and 8 weeks after the final inhalation (III). The three groups were compared according to clinical and laboratory parameters. The study examined the sustainability of the long‐term effect of the treatment after 8 weeks, as well as the tolerability of the formula as a double dose. Results: The CpGsd resulted in a significant improvement in 82% of the parameters, the CpGdd in 72%. In the long‐term evaluation, the CpGsd showed a significant improvement in 100% of the parameters in comparison to the initial values, the CpGdd in 67%. On the immunological level, the bronchoalveolar lavage revealed a significant reduction of IL‐4, IL‐8, and interferon‐γ. Conclusion: Both CpG groups displayed significant improvements in clinical and laboratory parameters, especially regarding the long‐term effect of CpGsd. Doubling the CpG dose did not result in any improvement in comparison to the original single dose. On the immunological level, an anti‐inflammatory, as well as an immunomodulatory effect, apart from a Th2‐dominated immune response, could be observed. This immunomodulatory inhalation treatment could indicate a new possibility for human allergic asthma therapy. Abstract : Equine asthma represents a naturally occurring animal model for human allergic neutrophilic asthma. Inhalative nanoparticle‐bound cytosine‐phosphate‐guanosine (CpG‐GNP) immunotherapy, independent of specific allergens, has already shown promising clinical and immunological results in previous studies and offers the possibility of a causal treatment of the underlying mechanism of the disease. This study analyses the relationship between dose and response, and evaluates a possible long‐term effect. On the immunological level, an anti‐inflammatory, as well as an immunomodulatory effect, apart from a Th2‐ dominated immune response, could be observed. This immunomodulatory inhalation treatment could indicate a new possibility for human allergic asthma therapy.